Set of Oscillation Criteria for Second Order Nonlinear Forced Differential Equations with Damping - Ambarka Abdalla Salhin; Ummul Khair Salma Din; Rokiah Rozita Ahmad; Mohd Salmi Md Noorani (Discrete Dynamics in Nature and Society)
By employing a generalized Riccati technique and an integral averaging technique, some new oscillation criteria are established for the second order nonlinear forced differential equation with damping. These results extend, improve, and unify some known oscillation criteria in the existing literature.